Returns to Education in the Economic Transition : A Systematic Assessment Using Comparable Data - Flabbi, Luca; Paternostro, Stefano; Tiongson, Erwin R. (World Bank, Washington, DC, 2012)
This paper examines the assertion that returns to schooling increase as an economy transitions to a market environment. This claim has been difficult to assess as existing empirical evidence covers only a few countries over short time periods. A number of studies find that returns to education increased from the "pre-transition" period to the "early transition" period. It is not clear what has happened to the skills premium through the late 1990s, or the period thereafter. The authors use data that are comparable across countries and over time to estimate returns to schooling in eight transition economies (Bulgaria, Czech Republic, Hungary, Latvia, Poland, Russia, Slovak Republic, and Slovenia) from the early transition period up to 2002. In the case of Hungary, they capture the transition process more fully, beginning in the late 1980s. Compared to the existing literature, they implement a more systematic analysis and perform more comprehensive robustness checks on the estimated returns, although at best they offer only an incomplete solution to the problem of endogeneity. The authors find that the evidence of a rising trend in returns to schooling over the transition period is generally weak, except in Hungary and Russia where there have been sustained and substantial increases in returns to schooling. On average, the estimated returns in the sample are comparable to advanced economy averages. There are, however, significant differences in returns across countries and these differentials have remained roughly constant over the past 15 years. They speculate on the likely institutional and structural factors underpinning these results, including incomplete transition and significant heterogeneity and offsetting developments in returns to schooling within countries.